A comparative study of skin cell activities in collagen and fibrin constructs. Issue 9 (September 2016) - Law, Jia Xian; Musa, Faiza; Ruszymah, Bt Hj Idrus; El Haj, Alicia J; Yang, Ying
Highlights: Keratinocytes and fibroblast demonstrated different cellular activities within two types of gel construct. Collagen gels with keratinocytes and fibroblasts have reduced mechanical strength. Fibrin gels with keratinocytes and fibroblasts showed stable mechanical strength. Nanofibers mesh increased fibroblast proliferation when keratinocytes were absence. Abstract: Collagen and fibrin are widely used in tissue engineering due to their excellent biocompatibility and bioactivities that support in vivo tissue formation. These two hydrogels naturally present in different wound healing stages with different regulatory effects on cells, and both of them are mechanically weak in the reconstructed hydrogels. We conducted a comparative study by the growth of rat dermal fibroblasts or dermal fibroblasts and epidermal keratinocytes together in collagen and fibrin constructs respectively with and without the reinforcement of electrospun poly(lactic acid) nanofiber mesh. Cell proliferation, gel contraction and elastic modulus of the constructs were measured on the same gels at multiple time points during the 22 day culturing period using multiple non-destructive techniques. The results demonstrated considerably different cellular activities within the two types of constructs. Co-culturing keratinocytes with fibroblasts in the collagen constructs reduced the fibroblast proliferation, collagen contraction and mechanical strength at late culture point regardless of the presence of nanofibers. Co-culturing keratinocytes with fibroblasts in the fibrin constructs promoted fibroblast proliferation but exerted no influence on fibrin contraction and mechanical strength. The presence of nanofibers in the collagen and fibrin constructs played a favorable role on the fibroblast proliferation when keratinocytes were absent. Thus, this study exhibited new evidence of the strong cross-talk between keratinocytes and fibroblasts, which can be used to control fibroblast proliferation and construct contraction. This cross-talk activity is extracellular matrix-dependent in terms of the fibrous network morphology, density and strength.